How Does Economic Education Promote Students' Learning Creativity? - Suparno Suparno; Ari Saptono; Agus Wibowo; Susan Febriantina (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2022)
This research is conducted to determine the process of how economic education shapes students’ learning creativity in the industrial revolution 4.0 era. Exploratory factor analysis and confirmatory factor analysis of AMOS 25 were employed as the method of research, while primary data was gathered through a survey using a questionnaire. The sample involved 120 students of the Faculty of Economics, Universitas Negeri Jakarta. The results show that (1) economic education significantly and positively affects digital economic literacy (2) economic education positively and significantly affects students' learning creativity (3) digital economic literacy positively and significantly affects students' learning creativity (4) digital economics literacy mediates positively and significantly the effect of economic education on students' learning creativity.Keywords: digital economic literacy, economic education, students' learning creativity, industrial revolution 4.0